2019
DOI: 10.1002/bmb.21287
|View full text |Cite|
|
Sign up to set email alerts
|

Flexible Implementation of the BASIL CURE

Abstract: Course-based Undergraduate Research Experiences (CUREs) can be a very effective means to introduce a large number of students to research. CUREs are often an extension of the instructor's research, which may make them difficult to replicate in other settings because of differences in expertise or facilities. The BASIL (Biochemistry Authentic Scientific Inquiry Lab) CURE has evolved over the past 4 years as faculty members with different backgrounds, facilities, and campus cultures have all contributed to a rob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 26 publications
0
37
0
Order By: Relevance
“…A recent article by Bell et al suggested the need for CUREs that focus on protein biochemistry 19 . Two such CUREs were mentioned at the IUBMB Education Conference 2019: the Malate Dehydrogenase CURE Community (http://home.sandiego.edu/~josephprovost/MCC.html) and BASIL, 20 a project involving the author and faculty members on 14 campuses.…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations
“…A recent article by Bell et al suggested the need for CUREs that focus on protein biochemistry 19 . Two such CUREs were mentioned at the IUBMB Education Conference 2019: the Malate Dehydrogenase CURE Community (http://home.sandiego.edu/~josephprovost/MCC.html) and BASIL, 20 a project involving the author and faculty members on 14 campuses.…”
Section: Figurementioning
confidence: 99%
“…BASIL (Biochemistry Authentic Scientific Inquiry Lab) is a CURE where students focus on predicting protein function, 20 using in silico (sequence alignment, structure alignment, and docking) and in vitro approaches (protein expression, purification, quantitation, SDS‐PAGE, enzyme activity and kinetics) to explore individual protein structures (Figure 1). Some methods are well established, but even simple methods have potential pitfalls.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…The camp was designed and directed by members from the IQB and the RCSB Protein Data Bank, facilitated by nine mentors from Rutgers and six mentors associated with the BASIL Consortium (https://basilbiochem.github.io/basil/index.html 6 ). Student researchers were selected from the RISE program at Rutgers (https://www.rise.rutgers.edu/), from other Rutgers‐affiliated programs, and from the campuses of the BASIL mentors.…”
mentioning
confidence: 99%